2021
DOI: 10.1016/j.aninu.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal thermal stress on oxidative status, immune response and stress hormones of lactating dairy cows

Abstract: This study aimed to assess the impact of seasonal thermal stress on oxidative stress, immune response, and stress hormones of lactating dairy cows in subtropical regions with different levels of temperature-humidity index (THI). A total of 32 healthy lactating Holstein dairy cows experienced 4 seasons (8 cows/season). The physiological parameters were categorized into low THI (LTHI, THI = 42.97 ± 0.95) in winter, moderate THI (MTHI, THI = 61.84 ± 0.42) in spring and autumn, and high THI period (HTHI, THI = 86.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
(64 reference statements)
0
23
0
1
Order By: Relevance
“…The NZ recordings were made outdoors over winter with average an average daytime temperature of 10.2 • C (range 2-18 • C) and overnight average of 8.4 • C (range 2-14 • C). Seasonal thermal stress has been found to affect behaviour, stress and immune response in dairy cows [32,33], and increasing temperature humidity index has been associated with decreased HRV measures in sheep and goats [34]. Although the cows in the winter conditions in NZ had higher HR and lower HRV than cows in summer conditions in Scotland, the environmental conditions could have affected the HR and HRV activity in this study.…”
Section: Discussionmentioning
confidence: 66%
“…The NZ recordings were made outdoors over winter with average an average daytime temperature of 10.2 • C (range 2-18 • C) and overnight average of 8.4 • C (range 2-14 • C). Seasonal thermal stress has been found to affect behaviour, stress and immune response in dairy cows [32,33], and increasing temperature humidity index has been associated with decreased HRV measures in sheep and goats [34]. Although the cows in the winter conditions in NZ had higher HR and lower HRV than cows in summer conditions in Scotland, the environmental conditions could have affected the HR and HRV activity in this study.…”
Section: Discussionmentioning
confidence: 66%
“…There were few reports on the effect of l ‐isoleucine and l ‐methionine supplementation on lactation performance of dairy cows under oxidative stress. However, it was reported that unhealthy cows (such as with inflammation or oxidative stress) need multiple nutrients to repair damage and indirectly lose some of their lactation properties (Li et al., 2021 , Memon et al., 2019 , Sordillo & Raphael, 2013 , Zahrazadeh et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that unhealthy cows (such as with inflammation or oxidative stress) need multiple nutrients to repair damage and indirectly lose some of their lactation properties (Li et al, 2021, Memon et al, 2019, Sordillo & Raphael, 2013, Zahrazadeh et al, 2018.…”
Section: Correlation Of Oxidative Stress-related Indicators and Metabolites With Milk Compositionmentioning
confidence: 99%
“…In this study, we show that the pregnancy rate in cows with subclinical mastitis in summer in the second lactation and in winter in the second and third lactations was lower than in cows without subclinical mastitis; while, there was no signi cant difference in the other seasons. Heat stress in summer and high humidity combined cold stress in winter could be responsible for reducing the pregnancy rate (Li et al 2021). In the mid lactation, only in the spring, high SCC was leading to high service per conception.…”
Section: Discussionmentioning
confidence: 99%